CT Features of Naviculocuneiform Coalitions - Kyung Ah Chun MD, PhD; Jin Soo Suh MD, PhD (Foot & Ankle Orthopaedics, 2018)
Category: Midfoot/Forefoot Introduction/Purpose: The purpose of our study was to evaluate and compare the CT features in patients with symptomatic and asymptomatic naviculocuneiform coalition Methods: We retrospectively reviewed the CT images of 37 naviculocuneiform coalitions in 26 patients (mean age 30 years). The 26 patients were 12 males and 14 females, with 19 right and 18 left feet, including 11 patients with bilateral coalition. The CT images were analyzed with regard to irregular articular surface, subchondral sclerosis, subchondral cyst, bone spur, joint space distance, loose body and bony fusion. The size of subchondral cyst was measured. The location and extent of joint involvement was also evaluated. CT features were compared between symptomatic and asymptomatic feet. Results: There were 20 feet (54%) in symptomatic group and 17 feet (46%) in asymptomatic group. The mean size of the subchondral cyst was 6.3 mm in the symptomatic group and 2.5 mm in the asymptomatic group (statistically significant). Bone spurs were significantly more common in the symptomatic group (11 of 20 feet) than in the asymptomatic group (2 of 17 feet) (p < 0.01). All 8 feet received operative treatment had subchondral cysts (mean size 6.7 mm) or bone spurs. Irregular articular surfaces were seen in all feet. Subchondral sclerosis, joint space distance, loose body, location and extent of joint involvement did not differ statistically significantly between two groups. Conclusion: Because of a statistically significant overlap of CT features, only large subchondral cysts and bone spurs can be more commonly detected with CT in the symptomatic feet compared to the asymptomatic feet, and may indicate aggressive treatment in patients with naviculocuneiform coalition.